(untitled) (Scientific journal of the Fergana State University, 2024)
The main resource used in the drying process is based on hot air. This leads to an increase in the cost of dried products, various damages to human health, and the loss of beneficial vitamins in the composition of dried products. Drying products through a specially coated ceramic quartz tube under the influence of infrared radiation serves to eliminate a number of the aforementioned shortcomings. The pulsed infrared radiation emitted from the specially coated ceramic quartz tube causes the natural evaporation of water in the product. Based on the research results, various agricultural products, such as vegetables including potatoes, carrots, and onions, have been analyzed for processing outcomes. The analyses present the effects of drying speed, thickness, and the technical parameters of drying time. The physical processes occurring in the device, evaporation, and its impact on products, as well as the natural movement of moisture upwards, are established. The advantages of the ejector system are demonstrated, indicating its contribution to the quality drying of products and the preservation of their composition. The indicators of the thermocouple located in the device ensure the atmosphere during the drying process, provide uniform drying of the products, prevent damage to their external appearance, and ensure that the drying time is not extended. The automatic voltage control system serves to intensively dry products for specified durations.